Genotype by environment interactions and stability for grain yield and other agronomic traits in selected tef (Eragrostis tef) genotypes in North Eastern Ethiopia - Solomon Mitiku; Mulugeta Mamo; Yemata Beze (Agrosystems, Geosciences & Environment, 2025)
Abstract The genotype by environment interaction influences the selection and recommendation of cultivars. Multi‐environment varieties were conducted on 13 tef genotypes, including the standard and local checks at Sirinka, Jari, Woleh, and Alem ketema, in 2016 and 2017 main cropping seasons. The objective of the study was to identify stable and adaptable varieties for drought‐prone areas of the eastern Amhara region. The experiment was laid out in a randomized complete block design with three replications. The combined analysis of variance revealed highly significant differences (p < 0.01) among genotypes, environment, and genotypes by environment interaction for grain yield and yield‐related traits. The first four additive main effects and multiplicative interaction selections per environment indicated that DZ‐01‐354 × DZ‐CR‐37‐131 has the top‐performing genotypes in the grain yield throughout 8 environments. Genotype (DZ‐01‐354 × DZ‐CR‐37‐68) was the second‐ranking genotype. Based on the view of the genotype by environment interaction biplot the two genotypes were the ideal genotypes in terms of high‐yielding potential and stability compared to the rest of tested genotypes. Genotype DZ‐01‐354 × DZ‐CR‐37‐131 gave the highest grain yield (2.31 tonnes ha−1) which had 18.4% and 36.6% yield advantage over the standard and local check, respectively. As a result, the candidate variety was verified and officially released by the national variety release committee in 2019 with the name Mena for production in drought‐prone areas of Northeast Ethiopia and similar tef‐producing areas.